Development and validation of second derivative and synchronous spectrofluorimetric methods for determination of oxytocin and ergometrine maleate in their combined formulation - Rizk, Mohamed; El-Alamin, Maha Mahmoud Abou; Moawad, Mervat Isaac (European Journal of Chemistry, 2018)
Simple and sensitive second derivative and synchronous spectrofluorimetric methods have been developed and validated for the quantitative determination of oxytocin and ergometrine maleate in their pure and combined dosage forms. The methods are based on the derivatization reaction of oxytocin with fluorescamine reagent, which yielded a highly fluorescent compound measured at 486 nm after excitation at 390 nm. Ergometrine was directly measured in combination with oxytocin, since it exhibits native fluorescence at 421 nm after excitation at 300 nm. Quantitation of oxytocin in presence of ergometrine was also successful at 482 and 477 nm using second derivative and synchronous spectrofluorimetry, respectively. Different experimental parameters were studied and optimized. The relative fluorescence intensity versus concentration plot was rectilinear over the range of 0.04-0.75 and 5-100 ng/mL for oxytocin and ergometrine, respectively. The methods were successfully applied for the determination of both drugs in their prepared combined ampoules. The methods were validated and compared with the reference chromatographic method; they revealed good accuracy and reproducible results. The proposed methods showed high accuracy and sensitivity, with no requirement of multiple steps or previous chemical separation.